2003
DOI: 10.1101/lm.57403
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Person Recognition

Abstract: Rapidly identifying known individuals is an essential skill in human society. To elucidate the neural basis of this skill, we monitored brain activity while experimental participants demonstrated their ability to recognize people on the basis of viewing their faces. Each participant first memorized the faces of 20 individuals who were not known to the participants in advance. Each face was presented along with a voice simulating the individual speaking their name and a biographical fact. Following this learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
47
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 69 publications
5
47
0
1
Order By: Relevance
“…Although most studies of the involvement of the insular cortex in memory have investigated taste aversion and taste recognition, there is some evidence that the insular cortex is also involved in memory that is not based on taste, including object recognition and inhibitory avoidance . Such findings fit well with recent evidence of two brain imaging studies suggesting an involvement of the insular cortex in human face and tactile recognition (Paller et al 2003;Reed et al 2004). As glucocorticoids are known to also influence the consolidation of other forms of recognition memory (Okuda et al 2004;Roozendaal et al 2006c), the insular cortex (and possibly perirhinal cortex) may be a general target for glucocorticoids in influencing recognition memory consolidation.…”
Section: Discussionsupporting
confidence: 89%
“…Although most studies of the involvement of the insular cortex in memory have investigated taste aversion and taste recognition, there is some evidence that the insular cortex is also involved in memory that is not based on taste, including object recognition and inhibitory avoidance . Such findings fit well with recent evidence of two brain imaging studies suggesting an involvement of the insular cortex in human face and tactile recognition (Paller et al 2003;Reed et al 2004). As glucocorticoids are known to also influence the consolidation of other forms of recognition memory (Okuda et al 2004;Roozendaal et al 2006c), the insular cortex (and possibly perirhinal cortex) may be a general target for glucocorticoids in influencing recognition memory consolidation.…”
Section: Discussionsupporting
confidence: 89%
“…These findings provide compelling evidence that the IC is not engaged uniquely in the (associative) learning and recognition of taste, but that it plays a more general role in recognition memory. Such findings fit well with recent findings of two brain imaging studies suggesting an involvement of the IC in human face and tactile recognition (Paller et al 2003;Reed et al 2004), as well as with evidence that reversible or permanent lesions of the IC produce strong impairments in the consolidation of inhibitory avoidance and watermaze spatial learning Nerad et al 1996).…”
supporting
confidence: 90%
“…These findings provide compelling evidence that the IC is not engaged uniquely in the (associative) learning and recognition of taste, but that it plays a more general role in recognition memory. Such findings fit well with recent findings of two brain imaging studies suggesting an involvement of the IC in human face and tactile recognition (Paller et al 2003;Reed et al 2004), as well as with evidence that reversible or permanent lesions of the IC produce strong impairments in the consolidation of inhibitory avoidance and watermaze spatial learning Nerad et al 1996).It is well established that a network of temporal structures including the perirhinal, parahippocampal, and entorhinal cortices and the hippocampus participates in recognition memory. Our results suggest that the IC is part of this network, as it is highly involved in processing the consolidation of newly presented tastes and, as the present findings indicate, of objects.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…In a similar study, Paller and colleagues (Paller, Gonsalves, Grabowecky, Bozic, & Yamada, 2000; see also Paller et al, 2003) observed different effects. The authors compared processing of unfamiliar faces with processing of newly learned faces that either had been associated with a name and a piece of biographical information or had been learned in isolation without any accompanying information.…”
mentioning
confidence: 84%